Effects of dietary grape proanthocyanidins on the growth performance, jejunum morphology and plasma biochemical indices of broiler chicks. (24th October 2016) - Yang, J. Y.; Zhang, H. J.; Wang, J.; Wu, S. G.; Yue, H. Y.; Jiang, X. R.; Qi, G. H.
Abstract : Grape proanthocyanidins (GPCs) are a family of naturally derived polyphenols that have aroused interest in the poultry industry due to their versatile role in animal health. This study was conducted to investigate the potential benefits and appropriate dosages of GPCs on growth performance, jejunum morphology, plasma antioxidant capacity and the biochemical indices of broiler chicks. A total of 280 newly hatched male Cobb 500 broiler chicks were randomly allocated into four treatments of seven replicates each, and were fed a wheat–soybean meal-type diet with or without (control group), 7.5, 15 or 30 mg/kg of GPCs. Results show that dietary GPCs decrease the feed conversion ratio and average daily gain from day 21 to day 42, increase breast muscle yield by day 42 and improve jejunum morphology between day 21 and day 42. Chicks fed 7.5 and 15 mg/kg of GPCs show increased breast muscle yield and exhibit improved jejunum morphologies than birds in the control group. Dietary GPCs fed at a level of 15 mg/kg markedly increased total superoxide dismutase (T-SOD) activity between day 21 and day 42, whereas a supplement of GPCs at 7.5 mg/kg significantly increased T-SOD activity and decreased lipid peroxidation malondialdehyde content by day 42. A supplement of 30 mg/kg of GPCs has no effect on antioxidant status but adversely affects the blood biochemical indices, as evidenced by increased creatinine content, increased alkaline phosphatase by day 21 and increased alanine aminotransferase by day 42 in plasma. GPC levels caused quadratic effect on growth, jejunum morphology and plasma antioxidant capacity. The predicted optimal GPC levels for best plasma antioxidant capacity at 42 days was 13 to 15 mg/kg, for best feed efficiency during grower phase was 16 mg/kg, for best jejunum morphology at 42 days was 17 mg/kg. In conclusion, GPCs (fed at a level of 13 to 17 mg/kg) have the potential to be a promising feed additive for broiler chicks.